2016
DOI: 10.3109/13625187.2015.1137280
|View full text |Cite
|
Sign up to set email alerts
|

Midwives as drivers of reproductive health commodity security in Kaduna State, Nigeria

Abstract: Objectives: The significant improvement in the contraceptive prevalence rate in Kaduna State, Nigeria, from 8.4% in 2008 to 18.5% in 2013 is a notable achievement. This article analyses the role of midwives as drivers of reproductive health commodity security (RHCS) and their impact on contraceptive use in Kaduna State. Methods: The United Nations Population Fund (UNFPA) supported the bimonthly review resupply meetings facilitated by midwives at State and local government area (LGA) levels. The midwives delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 2 publications
0
7
0
1
Order By: Relevance
“…Recognition of the unmet need for family planning has prompted the Nigerian government to collaborate with local and international partners in promoting modern contraceptive uptake (13, 28). For instance, with the support of the Reproductive Health Commodity Security Technical Working Group, the federal government of Nigeria developed a strategic plan for 2011–2015 and declared contraceptives free of charge at all public health facilities (29). …”
Section: Discussionmentioning
confidence: 99%
“…Recognition of the unmet need for family planning has prompted the Nigerian government to collaborate with local and international partners in promoting modern contraceptive uptake (13, 28). For instance, with the support of the Reproductive Health Commodity Security Technical Working Group, the federal government of Nigeria developed a strategic plan for 2011–2015 and declared contraceptives free of charge at all public health facilities (29). …”
Section: Discussionmentioning
confidence: 99%
“…• Increased contraceptive prevalence rate (Nigeria) by engaging midwives in provision of family planning services [ 114 ]…”
Section: Resultsmentioning
confidence: 99%
“…An increasing of nurse/midwives health officers, the expected log number of modern contraceptive users was increased by 0.01 and 0.04 respectively. Several studies have confirmed to the key role of nurses/midwives and health officers in providing guidance and effective counseling, resulting in an increased number of modern contraceptive users [ 34 , 35 ]. Other studies have reported an increase in a couple–year protection following the engagement of midwives in family planning services in service delivery points [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have confirmed to the key role of nurses/midwives and health officers in providing guidance and effective counseling, resulting in an increased number of modern contraceptive users [ 34 , 35 ]. Other studies have reported an increase in a couple–year protection following the engagement of midwives in family planning services in service delivery points [ 34 , 35 ]. In Ethiopia, the involvement of health extension workers increased the contraceptive prevalence rate from 14 to 30% in 4 years [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation